The concept of common heritage of mankind and the genetic resources of the seabed beyond the limits of national jurisdiction - Scovazzi, Tullio (2007)
The main innovation included in the United Nations Convention on the Law of the Sea (Montego Bay, 1982; Unclos) is the concept of common heritage of mankind.1While other important new aspects of the Unclos, such as the exclusive economic zone or the regime relating to the protection of the marine environment, are the result of the natural evolution of international law of the sea, the concept of common heritage of mankind has a revolutionary character. It presupposes a third kind of regime which is different from both the traditional regimes of sovereignty, applicable in the territorial sea, and of freedom, applicable on the high seas.